Effectiveness Test of Aquaculture Systems: Green Water, Biofloc, and Aquaponic Systems on the Stress Response of Snakehead Fish (Channa striata) - Rizki, Rani Ria; Kanya, Maya Resta; Puteri, Rizki Eka; Prariska, Donny; Lestari, Siti; Guttifera; Sari, Selly Ratna (Aquaculture Department, University of Mataram, 2024)
Water quality is a key factor in the cultivation of snakehead fish (Channa striata) because it can influence the level of physiological stress that impacts the health and growth of the fish. Three cultivation systems commonly used to manage water quality sustainably are the green water system, biofloc, and aquaponics. All three have different approaches to recycling waste and maintaining the balance of the cultivation environment. This study aims to compare the effectiveness of the three systems in maintaining water quality and reducing physiological stress in snakehead fish. The method used was a Completely Randomized Design (CRD) with three treatments and three replications. The parameters observed included levels of ammonia, nitrite, nitrate, dissolved oxygen (DO), and blood glucose levels as an indicator of stress. The results showed that the biofloc system produced the lowest blood glucose level (54 mg/dL), as well as the lowest nitrite and nitrate concentrations compared to the other treatments. Meanwhile, the biofloc system green water produces ammonia and dissolved oxygen (DO) levels, but biofloc is the most stable in maintaining water quality and the health of snakehead fish.